The Impact of COVID-19 Pandemic on People with Intellectual Disabilities: A Literature Review - Ghazi Maulana; Khalilullah Khalilullah; Intan Qanita; Amanda Yufika (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2021)
The ongoing coronavirus disease 2019 (COVID-19) pandemic has affected the global population, especially the vulnerable groups such as children, the elderly, indigenous people, and people with disabilities. Restriction and limited access to education, health, and public services due to measures taken to cope with the pandemic have made life even more difficult for people with disabilities, particularly those with intellectual ones. People with intellectual disabilities were not counted as a high-risk population, thus being excluded in most public health measurements that are done to encounter the pandemic. Several investigations have been conducted to explore the impacts of the COVID-19 pandemic on children, women, and the elderly, yet very few discussed how pandemics affected people with intellectual disabilities. This article is a review of existing literature using Medical Subject Headings (MeSH) keywords like “COVID-19” and “intellectual disabilities” which was conducted in Pubmed, Web of Science, Mendeley, Google Scholar and ResearchGate to find related studies. Here we reviewed studies on the impacts of the COVID-19 pandemic on people with intellectual disabilities, including access to education, healthcare, public services, and other related concerns. We also discussed the inclusivity of COVID-19 prevention and control measures taken so far and how it should be designed to accommodate people with intellectual disabilities. This review is expected to provide an insight for the stakeholders and policymakers to employ better and more inclusive approach in the management of pandemic to ensure the wellbeing and rights of people with disabilities in general and people with intellectual ones in particular.